Analysis of the Influence of Welfare, Motivation and Leadership Style on the Productivity of the Wholesale Archives Workforce of PT Griya Sumber Sejati - Rieky Ramadhan, Fickri; Tunggal Sari, Cahyani; Indriastuti, Ariyani (Sean Institute, 2025)
Labor productivity is measured by the results achieved compared to labor input, and increased productivity can drive increased sales. In the Wholesale Archives Workforce of PT Griya Sumber Sejati, Semarang City, there are problems with low productivity such as slow implementation of tasks and lack of motivation. This problem is also caused by inconsistent leadership in decision making, as well as lack of monitoring and inadequate income such as salary and incentives. The purpose of this study was to analyze the effect of employee welfare, work motivation, and leadership style on work productivity at PT Griya Sumber Sejati. This study involved 35 wholesale archives workers of PT Griya Sumber Sejati who were taken through a saturated sampling method and a survey was conducted using a questionnaire distributed through Google Forms. The data collected will be analyzed using the Partial Least Square (PLS) method and the SmartPLS version 4.0 application. The results of this study indicate that Welfare and Leadership Style do not have a significant effect on Productivity, while Motivation has a significant effect on Work Productivity